THE ROLE OF NOVELS IN LEARNING ENGLISH - Xolmatova Hamrobi shermurod qizi; Payziraxmonova Setora Muhammadali qizi (JOURNAL OF NEW CENTURY INNOVATIONS, 2024)
"This article discusses the importance of literary works in learning foreign languages and their role in enhancing the spiritual potential of readers." Literary works hold immense value in the process of learning a new language. They serve not only as a tool for enhancing vocabulary but also provide context for cultural understanding, analytical thinking, and more engaging learning experiences. Below are several ways in which literary texts contribute to language acquisition: